Development of an information support methodology for quality assessment of the prepress process - Hrabovskyi, Yevhen; Minukhin, Sergii; Brynza, Natalia (Eastern-European Journal of Enterprise Technologies, 2022)
A methodology for improving the information support of the prepress system by introducing new information blocks to prevent errors and predict the final result before the start of prepress operations is presented. Conceptual provisions for assessing the quality of the prepress process have been developed. These conceptual provisions have become the basis for solving the problem of systemic and random errors at the planning stage, created conditions for a significant reduction in prepress time. This parameterized form allows a formal description of operations, the determination of relevant quality indicators based on the formed parameters, and the development of databases and knowledge of the information support system for the anticipatory quality control of prepress. Classification of factors that affect the quality of the prepress process was carried out. As a result, it is possible to exclude from further consideration the factors that are not important for assessing the prepress quality. The proposed factors form the basis of the knowledge base of the information system for assessing the quality of the prepress process. The method of “anticipatory” quality control was developed. This method provides the detection of “bottlenecks” in each technological operation of the prepress process, as a result of which random and system errors can be avoided. The resulting indicators of the proposed method are the probability of an error, the probability of error-free execution of the technological operation, the cost of controlling the technological operation, and the cost of eliminating the error. The information support method for the quality assessment of the prepress process is proposed. Implementation of the developed information support methodology for assessing the quality of the prepress process in the form of an information system for assessing the prepress quality was carried out. This information system allows automating the method of “anticipatory” quality control proposed in this study. Thus, on the example of the technological operation of color correction and color separation by the “CMYK color model” parameter based on the use of the expert knowledge base subsystem, the probability of an error is 1, and the cost of eliminating the error is 6.